Coffee berry and green bean chemistry – Opportunities for improving cup quality and crop circularity. (January 2022) - Hall, Robert D.; Trevisan, Fabio; de Vos, Ric C.H.
Graphical abstract: Highlights: Green bean composition must be studied in the context of the whole berry. Our knowledge of green bean and berry chemistry is fragmented. Green bean chemistry is impacted by multiple genetic, environmental and cultivation practices. Crop circularity has great potential but depends on deeper chemical knowledge. Abstract: Coffee cup quality is primarily determined by the type and variety of green beans chosen and the roasting regime used. Furthermore, green coffee beans are not only the starting point for the production of all coffee beverages but also are a major source of revenue for many sub-tropical countries. Green bean quality is directly related to its biochemical composition which is influenced by genetic and environmental factors. Post-harvest, on-farm processing methods are now particularly recognised as being influential to bean chemistry and final cup quality. However, research on green coffee has been limited and results are fragmented. Despite this, there are already indications that multiple factors play a role in determining green coffee chemistry – including plant cultivation/fruit ripening issues and ending with farmer practices and post-harvest storage conditions. Here, we provide the first overview of the knowledge determined so far specifically for pre-factory, green coffee composition. In addition, the potential of coffee waste biomass in a biobased economy context for the delivery of useful bioactives is described as this is becoming a topic of growing relevance within the coffee industry. We draw attention to a general lack of consistency in experimentation and reporting and call for a more intensive and united effort to build up our knowledge both of green bean composition and also how perturbations in genetic and environmental factors impact bean chemistry, crop sustainability and ultimately, cup quality.